1998
DOI: 10.1007/s001050050807
|View full text |Cite
|
Sign up to set email alerts
|

Erythrokeratodermia progressiva symmetrica Darier-Gottron mit generalisierter Ausprägung

Abstract: A mother and her son presented with erythrokeratodermia progressiva symmetrica Darier-Gottron. Both patients developed symmetrical erythematous and hyperkeratotic plaques on the extremities and face at the age of 6 months. At the age of 2 1/2 years the son suffered from rapid progression of the disease to involve the entire skin. The disease of his mother had shown a similar course, however, with spontaneous regression at the age of 10 years. The clinical features of this generalized condition were identical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Our propositus was initially diagnosed as having PSEK, based on the presence of non‐migratory progressive erythematous and hyperkeratotic skin patches [Emmert et al, 1998]. We have recently argued that there is no clinical basis to distinguish PSEK as a separate nosological entity [Van Steensel, 2004a].…”
Section: Discussionmentioning
confidence: 99%
“…Our propositus was initially diagnosed as having PSEK, based on the presence of non‐migratory progressive erythematous and hyperkeratotic skin patches [Emmert et al, 1998]. We have recently argued that there is no clinical basis to distinguish PSEK as a separate nosological entity [Van Steensel, 2004a].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Several authors accept the existence of a nonmigratory but progressive erythrokeratoderma, called progressive symmetric erythrokeratoderma (PSEK) or Gottron erythrokeratoderma. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] However, it has been demonstrated that within sibships, erythrokeratodermas can be static or migratory and can even pass from one state to another, indicating that their distinction may not be valid. 24 Furthermore, the nosology has been muddled by confusion about what 'keratoderma' means, with the term used both for the peculiar starfish lesions of Vohwinkel's syndrome and loricrin keratoderma as well as the scaling hyperkeratosis of erythrokeratoderma variabilis.…”
Section: Discussionmentioning
confidence: 99%
“…Cases have been described without mutations in any of these genes 7–9 . Several authors accept the existence of a nonmigratory but progressive erythrokeratoderma, called progressive symmetric erythrokeratoderma (PSEK) or Gottron erythrokeratoderma 10–23 . However, it has been demonstrated that within sibships, erythrokeratodermas can be static or migratory and can even pass from one state to another, indicating that their distinction may not be valid 24 .…”
mentioning
confidence: 99%
“…The picture is further confused with the description by Emmert and colleagues of a mother and young son, both of whom had by the age of 6 months developed symmetrical erythematous hyperkeratotic plaques, completely consistent with PSEK, on the extremites and face 80 . In each patient, however, the disease progressed in early childhood to involve the entire skin in an eruption, which was entirely consistent with lamellar ichthyosis.…”
Section: Unresolved Issues: Is the Classification Watertight?mentioning
confidence: 63%